Avaliação da frequência de dermatoses em pacientes receptores de transplante renal e em pacientes com doença renal crônica acompanhados no hospital das clínicas da Universidade Federal de Minas Gerais - Érica Cristina Vieira (2021)
Background: The prevalence of chronic kidney disease (CKD) has increased in recent decades, as well as the number of patients with terminal CKD requiring transplantation. There are skin diseases more frequent in both populations. The purpose of the study was evaluate the frequency of dermatological disorders in renal transplant recipients (RTR) and in patients with CKD in conservative treatment. Methods: this observational and cross-sectional study recruited consecutive patients with CKD and RTR at the Nephrology Service and referred to the Dermatology Service of the Hospital das Clínicas da Universidade Federal de Minas Gerais (HC-UFMG), Brazil, between 2015 and 2020. Dermatoses were divided into four groups: benigns; infectious; pre-neoplastic and neoplastic. Groups were stratified by age in subgroup 1 (18 – 39 years old), subgroup 2 (40 – 59 years old) subgroup 3 (≥ 60 years old). Results: Overall 308 participants were included, 206 RTR (66.9%, median age 48 years, interquartile range [IQR] 38.0-56.0, 63.6% men) and 102 CKD patients (33.1%, median age 61.0, IQR 50.0-71.2, 48% men). Infectious skin diseases were observed in 39.3% in RTR group and 21.6% in CKD group (P=0.002). Human papillomavirus (HPV) related diseases were more prevalent in immunosuppressed patients when compared with patients with CKD, in subgroup 3 (23.5% vs 3.6%, P=0.005). Neoplastic skin lesions were present in nine (4.4%) RTR and only one (1.0%) subject in the CKD group. Among RTR, basal cell carcinoma to squamous cell carcinoma ratio was 2:1. There was a higher prevalence of azathioprine use in RTR with non-melanoma skin cancer when compared to those who did not have skin cancer and have used the same medication (66.7% vs 20.3% P= 0.005). Of the RTR who had HPV infection, 42.9% used azathioprine when compared with 20.0% who did not have HPV (P=0.026). Conclusions: This study demonstrated in patients monitored in a reference center in nephrology and in renal transplantation were found 39.3% and 21.6% of skin infectious diseases in RTR and in subjects with CKD respectively. Multi-professional team, must know to diagnose, treat and prevent skin disease in these populations.